Student attitudes and barriers of undergraduate pharmacy students towards scientific research: A preliminary study - E. Zainudin, Engku Nuraishah Huda; Khin Soe, May (2020)
This study aimed to evaluate attitudes and barriers towards scientific research among undergraduate pharmacy students. This preliminary descriptive study took place between August and December 2018 and included 200 students of year 3 and year 4 from Kuliyyah of Pharmacy in IIUM, Kuantan. A validated questionnaire survey with 15 close-ended questions and two open-ended questions were designed to evaluate students’ attitudes and barriers towards research. Responses were scored on a 5-point Likert scale. A total of 200 students participated in the study (response rate: 90%). Of these, 150 (75%) were female. A positive attitude towards research was reported by 80% of the students. No statistically significant differences were observed between genders with regards to attitudes towards and available resources for research (P = 0.500 and 0.200, respectively). Our result shows that the senior (Year 4) students had a significantly more positive attitude towards research compared to year 3 students (P = 0.005). A total of 78% students agreed that research is important for student and that they had sufficient resources for research. The participants reported barriers to embark on research included time management restrictions (n = 80; 40%), lack of research mentors (n = 30; 15%), lack of formal research analysis/methodology training (n = 20; 10%) and troubles in conducting literature searches (n = 20; 10%). According to the survey, pharmacy students had a positive attitude towards scientific research. Participants reported that research is relevant for their course, and the students need more formal training. The result of this study could be the basis for future study which may encourage positive research attitudes among student. Attention should be given to minimize the barriers identified in this study.